A π-CLCL Type Immittance Converter for Constant Current and Dynamic Load Applications - M. Abdur Razzak; Sumaiya B. Afzal; Meeyad M. Shabab (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Impedance-admittance converter is shortly termed as immittance converter. In this converter, the output current is proportional to the input voltage and the output voltage is proportional to the input current. The output current is thus independent of the load. This research evaluates the characteristics of a proposed π-CLCL immittance converter, which is a combination of the typical π- and T-type configurations, for constant current and dynamic load applications. The input-output characteristics and efficiency characteristics are analyzed and simulated. The characteristics are compared to that of the typical π- and T-type converters. The input-output characteristics and efficiency characteristics are then examined experimentally. It is observed that the experimental results agree with those of the simulation ones, and confirm that the π-CLCL configuration is more efficient than the typical π- and T-type immittance converters while maintaining a nearly constant output current and thus applicable for dynamic loads.DOI:http://dx.doi.org/10.11591/ijece.v4i5.5957